The role of passive cooling in the thermal balance of the ground and in improving the efficiency of a ground-source heat pump system - Chmielewska, Agnieszka; Stefanowicz, Ewelina; Sawicka, Julia (Instal, 2025)
This paper presents an analysis of the impact of ground heat regeneration on the efficiency of a ground source heat pump (GSHP) system in a residential building located in Wrocław, Poland. Based on a dynamic energy model developed in TAS EDSL and a borehole heat exchanger simulation using Earth Energy Designer , two system variants were compared: one with passive cooling (free-cooling) and other without passive cooling. The results show that regeneration of ground heat exchanger during the summer allows for higher brine inlet temperature, stabilized heat pump operation, and improved seasonal performance factor (SCOPon). Passive cooling also enhances indoor thermal comfort at a relatively low energy cost. The study confirms the importance of designing GSHP systems with integrated summer regeneration as a means to improve long-term energy efficiency and environmental performance.
Keywords: ground source heat pump; ground heat exchanger; free-cooling; passive cooling; EDSL TAS; Earth Energy Designer